Finding Literal Meaning in Manisnya Rambutan Kampungfrom the Perspective of Roland Barthes's Symbolic Code - Clement, Joyana Dilam (Malay Literature, 2020)
This study aims to review the literal meaning of Zahari Affandi's Manisnya Rambutan Kampung . The focus of this research is the interpretation of the literal meaning presented by the writer through the use of symbols. The objectives of this study are to identify the significance of the literal meaning to the community, to analyze the literal meanings in the text from the symbolic code perspective, as well as to evaluate the extent to which the literal meanings in the text conform to connotative properties from this perspective. This research was carried out using a simple qualitative method. The data collected was each illustration of events that employed signs or symbols. Therefore, the research was performed using the Semiotic Theory of Roland Barthes, which focuses on the use of symbols. The present research uses this theory to explore the meanings of signs in a more detailed way in all instances that contain elements of signifiers and signifieds in the literary work. This is due to the fact that the symbols used by the writer in the work have both a literal and implied meaning. Based on the research, we conclude that Zahari Affandi inserted several symbols with their own meaning in his work to convey certain messages. Keywords: Barthes, semiotics, symbolic code, sign, signified, Zahari Affandi